Influence of complex treatment with use of metformin on the production of the p53 in the patients with type 2 diabetes and metabolic syndrome - E. N. Chernysheva; T. N. Panova (Кубанский научный медицинский вестник, 2015)
The study included 41 patients aged 50.0 (39.0, 55.0) years, of which 29 men (70.7%) and 12 women (29.3%) with diabetes type 2 and metabolic syndrome in terms of voluntary informed consent. We studied the effect of combined treatment (correction of physical activity, the formation of healthy food, metformin) for the maintenance of premature aging markers p53 protein in these patients. Apoptosis was studied by determining serum - p53 (U/ml) by ELISA. In patients with type 2 diabetes and metabolic syndrome increased apoptosis - the content of p53 in the serum reaches 1,9 (1,79; 2,3) U/ml. Against the background of complex treatment of the protein content decreased to 0,98 (0,93; 1,1) U/ml.